Legal Analysis of Marriage Dispensation Requests for Minors in Cases of Premarital Pregnancy (Case Study: Decision No. 82/PDT.P/2024/PA.PROB) - Zachary, Rizky Is’Ad; Nurhayani, Nurhayani (Journal of Law and Economics, 2025)
This study investigates the dispensation of marriage for minors, a request for leniency granted by the Religious Court to prospective brides and grooms who are not yet of legal age to marry. This study intends to examine the basis for consideration used by judges in deciding and granting requests for marriage dispensation in Decision Number 82/Pdt.P/2024/PA.PROB, as well as examining the impact of marriage dispensation on mothers and children born, especially in the context of legal protection based on the Child Protection Law. In this study, a normative juridical approach is used to analyze the legal principles underlying the judge's decision and aspects of protecting children's rights. The findings suggest that the basis for judges' considerations is influenced by sociological and sharia factors, and assesses the principles of benefit and protection of the child's future. Furthermore, the impact of marriage dispensation on mothers and children carries the risk of violating children's basic rights, including the right to education, protection from violence, and the right to health, thus requiring serious attention from the legal protection system to ensure these rights are optimally protected. This research emphasizes the importance of a legal approach that prioritizes substantive justice and protection of vulnerable groups in the marriage dispensation decision-making process.